Thibaut de Champagne and Lyric Auctoritas in Paris, BnF fr. 12615. - O'Sullivan, Daniel E. (Textual Cultures: Text, Contexts, Interpretation (Society for Textual Scholarship))
Medieval composers and audiences alike took great stock in the cultural value of auctoritas, the notion that new compositions should closely follow the patterns set by previously accepted authors. The present study examines the concept as it applies to the composition of a particular manuscript: Paris, BnF fr. 12615. The codex underwent at least two, and most likely three, stages of compilation. Strategies of compilatio and ordinatio are examined to demonstrate how the compiler uses earlier songbooks dedicated to Thibaut de Champagne (d. 1253) to shape his own songbook and gradually move his anthology from aristocratic to urban, Artesian notions of auctoritas. Subsequent additions to 12615 enhance the original compiler's scheme.